Combined mechanical circulatory support for ventricular fibrillation in left ventricular assist device patient - Mahmood Abu Akel; Aviv A. Shaul; Gustavo R. Goldenberg; Yaron D. Barac; Binyamin Ben‐Avraham; Dan Gorfil; Dan Aravot; Tuvia Ben‐Gal (ESC Heart Failure, 2022)
Abstract Ventricular fibrillation, a life‐threatening ventricular arrhythmia, may result in pulselessness, loss of consciousness and sudden cardiac death. In this case report, we describe our experience in managing a 54‐year‐old man with HeartMate3 left ventricular assist device (LVAD) as a bridge to transplantation due to dilated non‐ischemic cardiomyopathy, presenting with incessant ventricular arrhythmia for 35 days despite multiple attempts to restore normal rhythm with external direct current cardioversion and anti‐arrhythmic medications. The patient remained stable in ventricular arrhythmia with no progression to asystole, but hemodynamic collapse due to right heart failure occurred in the third week. Combined use of two mechanical circulatory support devices (LVAD with VA ECMO) was needed to achieve haemodynamic and metabolic stability, eventually leading to successful heart transplantation in the index admission. The patient was discharged home 2 weeks after transplantation in good clinical condition.